Introduction to nonparametric detection with applications - Gibson, Jerry D. 1946-; Melsa, James L. (Electrical engineering, signal processing, 1996)
As a result, parametric detectors, which are excellent when model assumptions are satisfied, do not maintain the satisfactory performance necessary for detection